2008
DOI: 10.1177/1465116507085957
|View full text |Cite
|
Sign up to set email alerts
|

Regarding the Dutch `Nee' to the European Constitution

Abstract: A B S T R A C TIn June 2005, 61.5% of the Dutch voted 'nee' in the referendum on the European constitution. In the present contribution I test hypotheses from the national identity, utilitarian and political approaches to explain this voting behaviour. I collected data in the Netherlands to test whether one of those approaches has been decisive in explaining the referendum outcome. I also provide information about whether specific EU evaluations from these approaches explain the voting behaviour, thus bringing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…Swami and Furnham (2014) have highlighted a range of potentially relevant factors, including personality traits, and extreme paranoia and suspiciousness. Finally, it is important to highlight that our data are cross-sectional and, while we have interpreted our findings in line with contemporary theorizing (Gabel, 1998;Lubbers, 2008;de Vreese & Boomgaarden, 2005), some caution should be exercised when interpreting causational effects.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Swami and Furnham (2014) have highlighted a range of potentially relevant factors, including personality traits, and extreme paranoia and suspiciousness. Finally, it is important to highlight that our data are cross-sectional and, while we have interpreted our findings in line with contemporary theorizing (Gabel, 1998;Lubbers, 2008;de Vreese & Boomgaarden, 2005), some caution should be exercised when interpreting causational effects.…”
Section: Discussionsupporting
confidence: 66%
“…Academic research of Eurosceptic attitudes across Europe has broadly identified three core explanations, each identifying a set of non-mutually exclusive concerns as being the primary motive (de Vreese & Boomgaarden, 2005;Gabel, 1998;Lubbers, 2008). First, the political approach suggests that, given the low level of information about and knowledge of the integration process, voters resort to proxies when formulating their views about integration.…”
mentioning
confidence: 99%
“…Secondly, prior research has suggested that younger people tend to respond more flexibly to social change ( cf . Lubbers 2008; Lubbers and Scheepers 2007). Poland's communist experience, its subsequent national independence and its recent accession to the EU makes for a radically changing political context.…”
Section: European Identity Cross‐nationally: a Quantitative Analmentioning
confidence: 99%
“…‘[M]any groups of people among the member nations perceive the EU as a political organization which diminishes national state sovereignty, and [these groups] resist the EU's efforts at the creation of a “European identity” as directly at odds with their own, superordinate national identities’ (Wilson 1996:208). This perceived threat exists not only in politics, but has also been shown to be present in the media and society at large (see, for example, Lubbers 2008; Van Os 2008). The Dutch and French referenda in 2005 rejecting the proposed European constitution and the rejection of the revised constitutional treaty in Ireland in 2008 are still vividly present in Europe's recent political memory.…”
Section: Introductionmentioning
confidence: 99%
“…But another theme was that the Netherlands, a small country, was losing its autonomy and cultural identity within an enlarged EU and was being sidelined by the larger member states, that it was paying too much to Brussels, that the euro had hit consumers' pockets (Aarts and van der Kolk, 2006;Harmsen, 2005;Lubbers, 2008). Since this was the first Dutch referendum in modern times, the government had no experience of such campaigns, and the "no" campaigners appeared far more successful in taking the initiative and defining the agenda.…”
Section: The Dutch Rejectionmentioning
confidence: 99%